Simultaneous control and execution of public works in the gobierno regional de Cajamarca - Narro López, William Miguel (2025)
The objective of this study was to analyze the relationship between simultaneous control (SC) and the execution of public works (EPW) in the Gobierno Regional de Cajamarca, GRC (Regional Government of Cajamarca) during the year 2023. A quantitative approach with a non-experimental and cross-sectional design was used, employing a survey technique for which a structured questionnaire was applied, consisting of two scales: one to measure SC (17 items) and another to evaluate EPW (20 items). The validity of the content of the instrument was verified by three experts, and its reliability was verified using Cronbach's alpha coefficient, obtaining values of 0.849 for SC and 0.862 for EPW, indicating high internal consistency. Subsequently, the data were analyzed using Spearman's Rho correlation test (ρ Rho). The results revealed a very strong positive correlation between simultaneous control and EPW (Rho = 0.846; p = 0.000), a high positive correlation between concurrent control and EPW (Rho = 0.715; p = 0.001), and a moderate positive correlation between control visits and EPW (Rho = 0.559; p = 0.020). It is concluded that simultaneous control has a significant impact on improving efficiency, transparency, and the fulfillment of objectives in the execution of public works, and therefore its effective implementation is proposed as a strategic tool for strengthening regional public management.